Effect of multiple stress factors (thermal, nutritional and pregnancy type) on adaptive capability of native ewes under semi-arid environment. (July 2016) - Dias e Silva, Tairon Pannunzio; Costa Torreão, Jacira Neves da; Torreão Marques, Carlo Aldrovandi; de Araújo, Marcos Jácome; Bezerra, Leílson Rocha; kumar Dhanasekaran, Dinesh; Sejian, Veerasamy
Abstract: This study was conducted to evaluate the effect of multiple stress factors (thermal, nutritional and pregnancy type) on two different native track breeds of ewes as reflected by their adaptive capability under semi-arid environment. The multiple stressor experiment was conducted in twenty-four ewes (12 Santa Inês and 12 Morada Nova ewes). Both heat stress and pregnancy stress was common to all four groups. However, the animals were divided into further two groups within each breed on the basis of nutrition regimen. According the groupings were: Group 1 (Six Santa Ines ewes; heat stress; nutrition at 0.5% of BW; single pregnancy); Group 2 (Six Santa Ines ewes; heat stress; nutrition at 1.5% BW; twin pregnancy); groups Group 3 (Six Morada Nova ewes; heat stress; nutrition at 0.5% of BW; single pregnancy); Group 4 (Six Morada Nova ewes; heat stress; nutrition at 1.5% BW; twin pregnancy). All the animals in the experiment were pregnant. Heat stress was induced by exposing all animals to summer heat stress in outside environment while the nutritional regimen followed was at 0.5% and 1.5% level of body weight (BW) respectively in each breed. The experiment was conducted in a completely randomized design with two breeds, two nutritional treatments and two pregnancy types, 10 repetitions for physiological parameters and six for blood parameters, with repeated measures over time. Physiological parameters (respiratory rate, pulse rate and rectal temperature) were measured with the animals at rest in the morning and afternoon, 0600-0700 and 1300–1400 h, respectively, every seven days. Blood samples were collected every 14 d for determination of serum glucose, triglycerides, cholesterol, urea and creatinine. We found interaction effect between breed and pregnancy type on respiratory rate and rectal temperature with greater values in Santa Inês ewes than Morada Nova ewes. However, there was no significant fixed effect of pregnancy type and supplementation level on physiological responses of breeds. Environmental factor (period of the day) had influenced the physiological responses of ewes during all gestational period. Santa Inês ewes had greater serum glucose concentration at 105 d and 120 d of gestation compared to the Morada Nova ewes. Morada Nova ewes had greater concentrations of triglycerides, urea at 120 d, 150 d and also greater cholesterol at 105 d, 135 d and 150 d of gestation compared with Santa Inês ewes. The present result indicates that thermal condition was most important factor that modified the physiological responses of ewes in a semi-arid tropical environment. Highlights: This article evaluates the effect of multiple stress factors on pregnant ewes under semiarid conditions. Influence of the environment, nutritional and pregnancy type on physiological responses. There was a lack of influence of multiple stress factors on physiological responses. Native ewes had high adaptive capability these animals under semi-arid tropical environment.